The Influence of Omni-channel Strategy on Customers’ Repurchase Intention at Sociolla in Palu City with Customer Satisfaction as a Mediating Variable - Imanuela, Putri Tania; Ponirin, Ponirin; Muzakir, Muzakir; Nugraha, Mohammad Ega (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the influence of omnichannel strategy on repurchase intention with customer satisfaction as a mediating variable among Sociolla consumers in Palu. Using purposive sampling, 180 respondents who had shopped through more than one channel participated. Data were analyzed using SEM-PLS. Results show omnichannel strategy significantly impacts satisfaction (β = 0.911) and repurchase intention (β = 0.612). Satisfaction also influences repurchase intention (β = 0.346) and partially mediates the relationship. The findings highlight the importance of integrated customer experiences in fostering loyalty in digital beauty retail, especially in non-metropolitan regions.